Fame - Rowlands, Mark. (Montreal : McGill-Queen's University Press, 2008)
Annotation. "Mark Rowland s brings his philosophical expertise to bear on our concept of fame and explores the reasons behind its radical transformation. To understand this "new variant fame", Rowlands argues, we must engage in an extensive philosophical excavation that takes us back to a dispute that began in fourth-century BC Athens. Rowlands reveals that our present day notion of fame and the extremes that accompany it are symptoms of a significant cultural change: the decline of Enlightenment ideas has seen individualism eclipse objectivism about value, so much so that what characterizes Western society today is its constitutional inability to distinguish quality from bullshit. This, argues Rowlands, is the predicament in which we find ourselves today and which explains how fame can now be unconnected with any discernible distinction: we have lost any grip on the idea that there might be objective standards of evaluation even for some of the most important choices we make."--BOOK JACKET.
College Audience
Keywords: Fame; Celebrities; SOCIAL SCIENCE / General; Electronic books